2021
DOI: 10.3390/ijms22094757
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Polyurethane Composite Foams Reinforced with Plum Stones and Silanized Plum Stones

Abstract: In the following study, ground plum stones and silanized ground plum stones were used as natural fillers for novel polyurethane (PUR) composite foams. The impact of 1, 2, and 5 wt.% of fillers on the cellular structure, foaming parameters, and mechanical, thermomechanical, and thermal properties of produced foams were assessed. The results showed that the silanization process leads to acquiring fillers with a smoother surface compared to unmodified filler. The results also showed that the morphology of the obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
6
14
0
1
Order By: Relevance
“…The mean viscosity of each premixed polyols with the specific amount of CF filler is presented in Table 1 , as well as the results for the kinetic expansion for the produced RPUF composites. As expected, the greater amount of CF increased the dynamic viscosity significantly, with a higher result for CF 1 [ 3 ]. The higher reaction temperature is observed for CF 0.1, which can be related to the high contact between fillers and isocyanate, compared to the other groups.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The mean viscosity of each premixed polyols with the specific amount of CF filler is presented in Table 1 , as well as the results for the kinetic expansion for the produced RPUF composites. As expected, the greater amount of CF increased the dynamic viscosity significantly, with a higher result for CF 1 [ 3 ]. The higher reaction temperature is observed for CF 0.1, which can be related to the high contact between fillers and isocyanate, compared to the other groups.…”
Section: Resultssupporting
confidence: 65%
“…Bio-based filled rigid polyurethane foams (RPUF) are a new class of polymer composite materials that present interesting properties. Some recent studies on the field proved that when a vegetable fiber, or a filler, is introduced, as a second phase, the cellular composite presents increases of properties, such as thermal stability, fire resistance, and photodegradation performance [ 1 , 2 , 3 , 4 , 5 , 6 ]. Technological properties, as decreases of thermal conductivity, water/moisture uptake, greater dimensional stability, and aesthetical appearance, antibacterial/anti-aging properties are also achieved [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in characteristic foaming times can also be attributed to a higher dynamic viscosity of PUR foam mixtures with a higher content of SFP filler because it impedes the expansion and formation of larger cells. Very similar trends were observed in [ 33 ]’s study, where the authors incorporated silanised and non-treated plum stone filler into PUR foam compositions. Although, some natural raw materials such as natural cork have the opposite effect and reduce cream and gel times by 28% and 20%, respectively, and this phenomenon is attributed to the low thermal conductivity of cork agglomerates [ 34 ].…”
Section: Resultssupporting
confidence: 83%
“…For instance, PUR foam with SFP-20 has almost the same apparent density as LG-SFP-30 modified foam. The authors of [ 38 ] studied the impact of plum stone filler, silanized plum stone filler, and [ 3 ] algal cellulose on the performance of PUR foams and concluded that it could be attributed to the greater initial dynamic viscosity of PUR foams with unmodified filler particles.…”
Section: Resultsmentioning
confidence: 99%